Alzheimer’s disease genetics and ABCA7 splicing - Vasquez, Jared B. (J Alzheimers Dis, 2017)
Both common and rare polymorphisms within ABCA7 have been associated with Alzheimer’s disease (AD). In particular, the rare AD associated polymorphism rs200538373 was associated with altered ABCA7 exon 41 splicing and an AD risk odds ratio of ~1.9. To probe the role of this polymorphism in ABCA7 splicing, we used minigene studies and qPCR of human brain RNA. We report aberrant ABCA7 exon 41 splicing in the brain of a carrier of the rs200538373 minor C allele. Moreover, minigene studies show that rs200538373 acts as a robust functional variant in vitro. Lastly, although the ABCA7 isoform with an extended exon 41 is predicted to undergo nonsense mediated RNA decay, this was not supported by qPCR analyses, which showed relatively normal ABCA7 mRNA levels in the carrier of the rs200538373 minor C allele. In summary, rs200538373 is a functional polymorphism that alters ABCA7 exon 41 splicing without grossly altering the level of ABCA7 mRNA.